Considering ethical dilemmas related to brain death in newborns - Ilias Chatziioannidis; Georgios Mitsiakos (Hygeia Press di Corridori Marinella, 2014)
Brain death (BD), as the irreversible and permanent loss of cerebral and brainstem function, is relatively uncommon among newborns who need life support. It is considered the result of an acute and irreversible central nervous system insult. Asphyxia, severe intracranial hemorrhage and infection are the most common causes of  BD in children. BD diagnosis is usually based on clinical criteria. Dilemmas about life prolonging treatment for severely compromised infants - as brain dead infants are - has become challenging since neonatal intensive care unit (NICU) care has developed, quality of life and resource issues are nowadays continuously underlined. Caring for premature babies is expensive and costs have risen especially since an increased number of infants with handicaps survives. Intensivists' main duty is first to save lives and then to interrupt treatment in certain conditions like detrimental brain damage. The objective of this article is to present ethical decisions regarding brain dead newborns in order to balance between organ donation necessities and withholding/withdrawing treatment, with respect to the important role of infants' parents in the process.